Adrenomedullin Is Necessary to Resolve Hyperoxia-Induced Experimental Bronchopulmonary Dysplasia and Pulmonary Hypertension in Mice - Menon, Renuka T. (Am J Pathol, 2020)
Bronchopulmonary dysplasia (BPD)–associated pulmonary hypertension (PH) is an infantile lung disease characterized by aberrant angiogenesis and impaired resolution of lung injury. Adrenomedullin (AM) signals through calcitonin receptor–like receptor and receptor activity–modifying protein 2 and modulates lung injury initiation. However, its role in lung injury resolution and the mechanisms by which it regulates angiogenesis remain unclear. Consequently, we hypothesized that AM resolves hyperoxia-induced BPD and PH via endothelial nitric oxide synthase (NOS3). AM-sufficient (ADM(+/+)) or -deficient (ADM(+/−)) mice were exposed to normoxia or hyperoxia through postnatal days (PNDs) 1 to 14, and the hyperoxia-exposed mice were allowed to recover in normoxia for an additional 56 days. Lung injury and development and PH were quantified at different time points. Human pulmonary microvascular endothelial cells were also used to examine the effects of AM signaling on the NOS3 pathway and angiogenesis. Lung blood vessels and NOS3 expression decreased and the extent of hyperoxia-induced BPD and PH increased in ADM(+/−) mice compared with ADM(+/+) mice. Hyperoxia-induced apoptosis and PH resolved by PND14 and PND70, respectively, in ADM(+/+) mice but not in ADM(+/−) mice. Knockdown of ADM, calcitonin receptor–like receptor, and receptor activity–modifying protein 2 in vitro decreased NOS3 expression, nitric oxide generation, and angiogenesis. Furthermore, NOS3 knockdown abrogated the angiogenic effects of AM. Collectively, these results indicate that AM resolves hyperoxic lung injury via NOS3.